VALIDATION OF THE HULL GIRDER DEFLECTION OF A MULTIPURPOSE CARGO SHIP (ASEAN Engineering Journal, 2024)
When a ship encounters head-sea conditions, it can experience still water bending and wave-induced vertical moments. These moments can cause the hull girder to undergo longitudinal deflection, which can negatively impact the shaft alignment of the propulsion unit and the sealing of hatch covers and other onboard machinery. On the other hand, beam sea conditions can lead to transverse hull girder deflection, which is especially problematic for open-deck ships and can cause significant hatch-coming deflection. A numerical strength check has been performed using FEA software FEMAP with NX Nastran and an analytical review based on Euler-Bernoulli's beam theory to analyse the ship's strength. The ship is represented as a simply supported beam, and both analytical and numerical methods are used to calculate deflection for different sea conditions (head and beam seas). A mesh sensitivity analysis has been done to ensure the accuracy of the numerical analysis, and the results from both techniques are compared to validate their accuracy. Finally, a numerical analysis is conducted to confirm the accuracy of the analytical study when considering the ship as a complex structure. Overall, this research underscores the greater significance of longitudinal deflection over transverse deflection in the hull girder of a multipurpose cargo ship. Combining both approaches, a comprehensive understanding of the ship's hull girder strength and deflection behaviour is achieved, enhancing overall structural integrity and safety.